Frontline Science: Mast cells regulate neutrophil homeostasis by influencing macrophage clearance activity. Issue 4 (28th February 2019) - Jachetti, Elena; D'Incà, Federica; Danelli, Luca; Magris, Raffaella; Dal Secco, Chiara; Vit, Filippo; Cancila, Valeria; Tripodo, Claudio; Scapini, Patrizia; Colombo, Mario Paolo; Pucillo, Carlo; Frossi, Barbara
Abstract: The receptor tyrosine kinase cKit and its ligand stem cell factor are essential for mast cells (MC) development and survival. Strains with mutations affecting the Kit gene display a profound MC deficiency in all tissues and have been extensively used to investigate the role of MC in both physiologic and pathologic conditions. However, these mice present a variety of abnormalities in other immune cell populations that can affect the interpretation of MC-related responses. C57BL/6 Kit W-sh are characterized by an aberrant extramedullary myelopoiesis and systemic neutrophilia. MC deficiency in Kit W-sh mice can be selectively repaired by engraftment with in vitro-differentiated MC to validate MC-specific functions. Nevertheless, the impact of MC reconstitution on other immune populations has never been evaluated in detail. Here, we specifically investigated the neutrophil compartment in primary and secondary lymphoid organs of C57BL/6 Kit W-sh mice before and after MC reconstitution. We found that, albeit not apparently affecting neutrophils phenotype or maturation, MC reconstitution of Kit W-sh mice restored the number of neutrophils at a level similar to that of wild-type C57BL/6 mice. In vitro and ex vivo experiments indicated that MC can influence neutrophil clearance by increasing macrophages' phagocytic activity. Furthermore, the G-CSF/IL-17 axis was also influenced by the presence or absence of MC in Kit W-sh mice. These data suggest that MC play a role in the control of neutrophil homeostasis and that this aspect should be taken into account in the interpretation of results obtained using Kit W-sh mice. Graphical Abstract: Mast cell reconstitution of Kit(W-sh)/Kit(W-sh) sash mice attenuates neutrophilia by reduction of systemic levels of G-CSF and IL-17, and by enhancement of the macrophage-mediated neutrophil phagocytosis.